2021
DOI: 10.1126/sciadv.abg8387
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast, sensitive, and portable detection of COVID-19 IgG using flexible organic electrochemical transistors

Abstract: The outbreak of COVID-19 and its continued spread have seriously threatened public health. Antibody testing is essential for infection diagnosis, seroepidemiological analysis, and vaccine evaluation. However, convenient, fast, and accurate antibody detection remains a challenge in this protracted battle. Here, we report an ultrafast, lowcost, label-free, and portable SARS-CoV-2 immunoglobulin G (IgG) detection platform based on organic electrochemical transistors (OECTs), which can be remotely controlled by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
178
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 51 publications
1
178
0
1
Order By: Relevance
“…Xue et al reported an intelligent wearable face mask integrated with a flexible immunosensor for highly sensitive screening of exhaled coronavirus aerosols. In addition, some other kinds of on-site detection devices, such as the electrochemical biosensors, allow detection of multiple kinds of molecules, including antigens and antibodies with high sensitivity and specificity [ 160 , 161 , 162 , 163 ]. Yakoh et al reported a paper-based electrochemical biosensor for label-free detection of SARS-CoV-2 antibodies without the specific requirements of antibodies [ 164 ].…”
Section: Micro/nano Devices For Point-of-care Testing Of Sars-cov-2mentioning
confidence: 99%
“…Xue et al reported an intelligent wearable face mask integrated with a flexible immunosensor for highly sensitive screening of exhaled coronavirus aerosols. In addition, some other kinds of on-site detection devices, such as the electrochemical biosensors, allow detection of multiple kinds of molecules, including antigens and antibodies with high sensitivity and specificity [ 160 , 161 , 162 , 163 ]. Yakoh et al reported a paper-based electrochemical biosensor for label-free detection of SARS-CoV-2 antibodies without the specific requirements of antibodies [ 164 ].…”
Section: Micro/nano Devices For Point-of-care Testing Of Sars-cov-2mentioning
confidence: 99%
“…Markedly, Antibody and antigen surface proteins comprised of zwitterionic amino acid sequences with positively- or negatively-charged functional groups corresponding to the IEP and pH values of the electrolyte. Most of the therapeutic monoclonal antibodies (mAbs) in infected human serum, e.g., anti-SARS-CoV-2 IgG and anti-H1N1 IgG, suggest IEP values above 8.0 and thereby carry a slight net positive charge in phosphate-buffered saline (PBS) solution (pH 7.4) [25] . Moreover, each virion keeps its RBDs distribution, being consistent with specific cell receptors on the host cell’s membrane [6] .…”
Section: Detection Platform and Biosensing Mechanismmentioning
confidence: 99%
“…, polarity and dielectric constant) are brought into contact with or rubbed against each other, the charge neutrality disappears, and two surfaces acquire equivalent but opposite charges. Electrostatic charges induced on the back-electrodes further generate a potential drop, driving electrons to flow between the two electrodes [25] . Taking four operation modes of TENG into account, lateral sliding and freestanding modes require an additional surface modification such as superhydrophobicity for fluid-based TENGs [44] .…”
Section: Device Flexibility In Operation Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…FETs of this kind, based on organic semiconductor (OSC) active materials, have been successfully employed for both fundamental studies and for a variety of applications from electronics 1–7 to biology, 8–11 artificial intelligence, and biosensors and even for Covid-19 detection. 12,13 While the traditional silicon technology relies on expensive manufacturing processes and on the typical use of rigid and brittle materials that are unsuitable for cheap and flexible electronics, organic semiconductors are promising candidates for the next-generation of smart, portable and wearable devices. 1,14,15 The massive work carried out during the last three decades on the development of novel organic semiconductors, their controlled processing and device optimization made it possible to increase field-effect mobilities in organic transistors, reaching values up to 20 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%